Cooperation between CD4+ T Cells and Humoral Immunity Is Critical for Protection against Dengue Using a DNA Vaccine Based on the NS1 Antigen. - Antônio J S Gonçalves; Edson R A Oliveira; Simone M Costa; Marciano V Paes; Juliana F A Silva; Adriana S Azevedo; Marcio Mantuano-Barradas; Ana Cristina M A Nogueira; Cecília J Almeida; Ada M B Alves (Public Library of Science (PLoS), 2015)
Dengue virus (DENV) is spread through most tropical and subtropical areas of the world and represents a serious public health problem. At present, the control of dengue disease is mainly hampered by the absence of antivirals or a vaccine, which results in an estimated half worldwide population at risk of infection. The immune response against DENV is not yet fully understood and a better knowledge of it is now recognized as one of the main challenge for vaccine development. In previous studies, we reported that a DNA vaccine containing the signal peptide sequence from the human tissue plasminogen activator (t-PA) fused to the DENV2 NS1 gene (pcTPANS1) induced protection against dengue in mice. In the present work, we aimed to elucidate the contribution of cellular and humoral responses elicited by this vaccine candidate for protective immunity. We observed that pcTPANS1 exerts a robust protection against dengue, inducing considerable levels of anti-NS1 antibodies and T cell responses. Passive immunization with anti-NS1 antibodies conferred partial protection in mice infected with low virus load (4 LD50), which was abrogated with the increase of viral dose (40 LD50). The pcTPANS1 also induced activation of CD4+ and CD8+ T cells. We detected production of IFN-γ and a cytotoxic activity by CD8+ T lymphocytes induced by this vaccine, although its contribution in the protection was not so evident when compared to CD4+ cells. Depletion of CD4+ cells in immunized mice completely abolished protection. Furthermore, transfer experiments revealed that animals receiving CD4+ T cells combined with anti-NS1 antiserum, both obtained from vaccinated mice, survived virus infection with survival rates not significantly different from pcTPANS1-immunized animals. Taken together, results showed that the protective immune response induced by the expression of NS1 antigen mediated by the pcTPANS1 requires a cooperation between CD4+ T cells and the humoral immunity.